AEM_3e_Appendix2

AEM_3e_Appendix2 - Z xt x 1 ( e t ) dt = x Z t x 1 e t dt =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Appendices Appendix II Gamma Function 3. If t = x 3 , then dt =3 x 2 dx and x 4 dx = 1 3 t 2 / 3 dt .Now Z 0 x 4 e x 3 dx = Z 0 1 3 t 2 / 3 e t dt = 1 3 Z 0 t 2 / 3 e t dt = 1 3 Γ µ 5 3 = 1 3 (0 . 89) 0 . 297 . 6. For x> 0 Γ( x +1)= Z 0 t x e t dt u = t x ,du = xt x 1 dt ; dv = e t dt, v = e t = t x e t ¯ ¯
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Z xt x 1 ( e t ) dt = x Z t x 1 e t dt = x ( x ) . 310...
View Full Document

Ask a homework question - tutors are online